Identification of physical interaction between trimethoprim and sulfamethoxazole by contact method kofler and crystallization reaction - Zaini, Erizal (INDONESIAN JOURNAL OF PHARMACY, 2010)
Identification of solid state interaction between TMP and SMZ by hot contact method Kofler and crystallization reaction had been carried out. The results of hot contact method Kofler shown formation a new crystalline habit as long and thin needle shaped on contact zone (mixing zone) between Solid TMP and SMZ. It had a different melting point in compared to its single component. Crystallization reaction between two of supersaturated solution of component TMP and SMZ in methanol solvent also indicated the growth of crystal habit as similar as  hot contact method Kofler. Solid state interaction between TMP and SMZ was confirmed by microscopic SEM, powder X-ray diffraction, and thermal DSC. Microscopic analysis by SEM showed significantly the change of habit and morphology of  crystal as long and thin needle shaped. New powder X-ray diffraction (PXRD) interferences peaks were observed in addition to PXRD interference peaks of each component that proved formation of cocrystalline phase. Thermogram DSC indicated a new  endothermic peak corresponding to melting point of a new cocrystalline phase at temperature 178,82 °C.Key words : trimethoprim, sulfamethoxazole, physical interaction, cocrystalline phase